Validación de Alstroemeria parvula Phil. (Alstroemeriaceae) - MUÑOZ-SCHICK, MÉLICA; MORALES, VANEZZA; MOREIRA-MUÑOZ, ANDRÉS (Gayana Botánica, 2011)
Alstroemeria parvula Phil., is validated according to new recollections and observations in the Central Chilean Andes. It is redescribed and new localities are included confi rming that it is solely protected in the private reserve and RAMSAR Site “Parque Andino Juncal”.